The precipitation of nanocrystalline structure in the joule heated Fe72Al5Ga2P11C6B4 metallic glasses - Mitrović N.; Kane S.; Roth S.; Kalezić-Glišović A.; Mickel C.; Eckert J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, the evolution of the nanostructure on dc Joule heated Fe72Al5Ga2P11C6B4 metallic glass ribbons have been investigated. Heating power per square area (PS) was ranging between 0.8 to 7.1 W/cm2 in order to get various stages of relaxation or nanocrystallization. The crystallization starts after applying PS ≈ 4.35 W/cm2 and the sample consist of residual amorphous matrix, a magnetic crystalline component and also a non-magnetic crystalline component (relative abundance of Fe in the crystalline phase is about 35 %). XRD measurements show that crystalline samples after current annealing consist of Fe3B, FeC, FeP and Fe3P compounds. On TEM micrograph a broad distribution of shapes and sizes is noticed, the latter range from about 60 to 350 nm, increasing by applied heating power. The decrease of the electrical resistivity after each current annealing treatment is rather small in comparison with other Fe-based amorphous alloys (only about 1.5 % for the highest PS). Partial nanocrystallization leads to increase of coercive field (from HC ≈ 7 A/m in the amorphous as-cast state up to 45 A/m) attributed to precipitation of magnetically harder compounds (Fe3B and FeC).